The Protection of Women Asylum Seekers under the European Convention on Human Rights: Unearthing the Gendered Roots of Harm. (17th May 2018) - Peroni, Lourdes
Abstract: In this article I analyse women asylum seekers' claims of gendered ill-treatment under Article 3 of the European Convention on Human Rights. I argue that the European Court of Human Rights moves away from creating equal conditions of protection for women asylum seekers every time it adopts two modes of reasoning: under scrutinizing the gendered roots of risk of ill-treatment and over scrutinizing individual capacity to deal with the risk. The first mode of reasoning overlooks the social and institutional conditions that render women vulnerable to ill-treatment. The second mode over emphasizes a woman's ability to protect herself and/or male relatives' capacity to protect her. The two modes suggest that women asylum seekers risk ill-treatment because of personal failures/limits rather than socio-institutional failures/constraints. These modes of reasoning may oversimplify concrete risks and recreate women's subordinate status in human rights discourse. To counter these faults, in this article I propose to reappraise the risk of gendered ill-treatment structurally and relationally.